Hakikat Manajemen Pendidikan Islam untuk Tata-Kelola Universitas yang Baik: (Good Governance University) - Bahri, Saiful; Irwansyah, Irwansyah; Pahrudin, Agus (PT. Alahyan Publisher Sukabumi, 2024)
Islamic education management is an important aspect in establishing good university governance, which is integrated with the values ​​of justice, honesty, and accountability of Islamic teachings. This article analyzes the nature of Islamic education management and its relevance in university governance, using the literature study method. Islamic education management prioritizes organizing, planning, implementing, and supervising education to achieve comprehensive educational goals and focuses on character development. Amid challenges such as lack of transparency and stakeholder participation, an approach based on Islamic values ​​is expected to create a sustainable education system that is responsive to the needs of society. By implementing the principles of Islamic education management, higher education institutions can improve the quality of education and its relevance, as well as strengthen their role in developing quality human resources.